Validity and Practicality Test of Science Comic learning media for Class VI on Waste Processing Material at SDN 8 Pule Trenggalek - Hidayati, Nurul; Sri Utami; Raden Syaifuddin (Florea : Jurnal Biologi dan Pembelajarannya, 2024)
This study aims to measure the validity, practicality and effectiveness of science comic media with the material Processing Waste in class IV students at SDN 8 Pule, Pule District, Trenggalek Regency. This research is Development Research by adopting the ADDIE development model which has 5 stages, namely: Analysis, Design, Develop, Implement, and Evaluate. There are 4 validators, 2 from material experts and 2 from media experts. Practicality is measured by analyzing the results of respondents' (students') responses. The respondents in this study were 15 students consisting of 6 female students and 9 male students in class IV of SDN 8 Pule, Pule District, Trenggalek Regency. The effectiveness of learning with science media was analyzed using the N-gain formula. The results of the research show that the science comic media has an average validation value of 76 (Valid), which means it is suitable for use with revisions. The practicality percentage of the science comic media is 97% in preliminary activities, 100% in core activities, 97.2% in closing activities. The N-Gain value is 0.7 (high: 0.07-100) which means that the effectiveness of learning using science comic media is high or very effective, student response is very good (90%). Student learning outcomes in the critical thinking aspect increased from an average score of 30 to an average score of 80. Students looked active, enthusiastic and enthusiastic in answering every question asked by the teacher, and students looked enthusiastic in participating in every learning process.